Synthesis and cryogenic spectroscopy of narrow-diameter single-wall carbon nanotubes. (August 2016) - Hofmann, Matthias S.; Noé, Jonathan; Nutz, Manuel; Kneer, Alexander; Dehmel, Raphael; Schaffroth, Lilian; Högele, Alexander
Abstract: We report chemical vapor deposition and cryogenic photoluminescence studies of narrow-diameter single-wall carbon nanotubes. Our systematic study of synthesis parameters identifies means to control the average length, diameter, and areal density of carbon nanotubes grown on silica substrates. Using synthesis conditions that favor the growth of carbon nanotubes with sub-nanometer diameters, we fabricate samples with spatially isolated suspended nanotubes ideally suited for optical studies. Photoluminescence spectroscopy of individual nanotubes reveals two classes: spectrally broad and narrow single-peak emission at the temperature of liquid helium. The latter class with spectral line widths down to the resolution limit of our spectrometer of 40 μeV indicates that exciton coherence in carbon nanotubes can be substantially improved by controlling the growth conditions and utilized in sources of indistinguishable single photons.